2019
DOI: 10.1002/psc.3156
|View full text |Cite
|
Sign up to set email alerts
|

The dual functionality of antimicrobial peptides Os and Os‐C in human leukocytes

Abstract: Antimicrobial peptides (AMPs), Os and Os-C, have been identified as multifunctional peptides with antibacterial, antiendotoxin, and anti-inflammatory properties. For further development of Os and Os-C as therapeutic peptides, it is essential to evaluate these effects in human mononuclear (MN) and polymorphonuclear (PMN) leukocytes. The cytotoxicity and the effects of both peptides on MN and PMN morphology were determined with the Alamar-Blue assay and scanning electron microscopy, respectively. The ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…No significant differences in cell proliferation existed between the PLGA and PLGA/NAT-Os scaffolds, for both growth periods of 3 and 7 days, demonstrating the nontoxicity of the NAT-Os. Previous studies have shown that NAT-Os has good cellular compatibility and will not have any negative effect on eukaryotic cells 24 . The results of these studies are similar to the cell proliferation result in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant differences in cell proliferation existed between the PLGA and PLGA/NAT-Os scaffolds, for both growth periods of 3 and 7 days, demonstrating the nontoxicity of the NAT-Os. Previous studies have shown that NAT-Os has good cellular compatibility and will not have any negative effect on eukaryotic cells 24 . The results of these studies are similar to the cell proliferation result in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial peptides (AMPs) are an important part of the innate immune system of organisms and can reasonably solve the problem of bacterial resistance 23 . The short C-terminal peptide Os, from OsDef2, a defensin in the midgut of the soft tick Ornithodoros savignyi , has been studied in the literature 24 . The main antibacterial effects of Os is the destruction of the bacterial cell structure and the indentation of the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability is one of the most reliable assessments of the efficacy of AMPs, and has been widely applied in diverse studies [17,26,40,[50][51][52][53]. However, viability can be attributed to different causes, namely, loss of membrane integrity, reduced metabolism, among other factors, which leads to the need of assessing cell viability by resorting to different techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has no toxic effects on mammalian cells [14]. Although increasing evidences have shown that the AMPs can serve as a critical regulator for diverse biological events including immune responses [16][17][18][19], the mechanism behind the BMGlvA2-regulated immunity is just beginning to be explored.…”
Section: Introductionmentioning
confidence: 99%